AB0140 Relationship between Expression of Synovial B Cell Survival Factors and Clinical Response to Rituximab Treatment in Rheumatoid Arthritis. (10th June 2014) - Thurlings, R.; Boumans, M.; de Jager, W.; Vos, K.; van Baarsen, L.; Gerlag, D.; Prakken, B.; Tak, P.P.
Abstract : Background: Rituximab aims to deplete CD20 positive B cells and exerts a significant and often long-lasting clinical effect in a subset of patients with rheumatoid arthritis (RA). The extent of B cell depletion in the inflammatory tissues after rituximab varies between patients and persistence of plasma cells and plasma cell products is associated with clinical non-response. This suggests rituximab may fail to deplete pathogenic B cells. Objectives: To investigate whether the variable clinical response to rituximab might be explained by differential expression of B cell survival factors in the inflamed synovial tissue of RA patients. Methods: Twenty-four RA patients underwent an arthroscopic synovial biopsy before, 1 month after and 4 months after treatment with rituximab. Treatment was given via two infusions (1, 000 mg on day 1 and 15), both without methylprednisolon premedication to be able to study specific biological effects of rituximab. Clinical response was defined as a response according to the European League Against Rheumatism (EULAR) criteria at week 24. Peripheral blood and synovial tissue were analyzed for expression and levels of B cell survival factors: BLyS, APRIL, IL-1β, IL6, BLyS, VCAM, ICAM, IFNα, CXCL12 and BLIMP1. Correlation between baseline expression and changes in B cell survival factors and clinical response were calculated using logistic regression analysis. Results: We found no significant correlation between baseline expression level of synovial B cell survival factors and clinical response to treatment. After treatment, the expression levels of BLyS, APRIL, IL-1β, IL6, ICAM and BLIMP1 were unaltered. The expression of IFNα and VCAM decreased after treatment, of which VCAM within one month ( P =0.035, P =0.022 and P =0.039, respectively). In contrast, expression of CXCL-12 increased after treatment ( P =0.046). In clinical responders VCAM expression decreased further between 1 and 4 months after treatment, although a statistical significant difference with non-responders could not be detected. Conclusions: Clinical non-response to rituximab is not associated with a higher baseline expression of B cell survival factors in the inflamed synovial tissue of RA patients. However, the persistent expression of survival factors independent of the extent of B cell depletion may promote the persistence of pathogenic B cell subsets in clinical non-responders to treatment. Acknowledgements: Het Reumafonds Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5312